Hydrogen-peroxide and silicone-hydrogel contact lenses: Worsening of external eye condition and tear film instability. Issue 2 (April 2018) - Moro, A.; Fagnola, M.; Picarazzi, S.; Di Dio, A.; Pastori, V.; Lecchi, M.; Tavazzi, S.
Highlights: External eye worsening occurred in wearers of silicone-hydrogel CLs treated with H2 O2 . Worsening of tear stability occurred in CL wearers regardless of care system. Tear hydrodynamic diameter is affected by CL wear regardless of CL care system. Artificial tears prevent external eye worsening and tear instability. Abstract: Purpose: The aim is discussing the origins of worsening of external eye condition (EEC) and of tear film (TF) instability after wear of silicone-hydrogel contact lenses (CLs) with hydrogen-peroxide (H2 O2 ) care system. Methods: EEC and TF stability were evaluated before and after 15 days of wear combined with different care systems: (1) H2 O2, (2) detergent solution and H2 O2, (3) multipurpose solution (MPS), (4) H2 O2 and artificial tears. In-vitro cell mortality tests were performed after 24 h cell incubation with CLs treated with H2 O2 . Photon correlation spectroscopy (PCS) was carried out on tears of non-wearers and CL wearers who used MPS or H2 O2 solution. Results: Worsening of EEC was observed only for the group using H2 O2 (group 1). In-vitro, cell mortality was found higher for worn CL than for unworn CLs. Worsening of TF stability was observed regardless of care system and also PCS results on tears of CL wearers were found different compared to non-wearers regardless of care system. The only observed remedy for tear instability of CL wearers was found to be the administration of artificial tears. Conclusions: Worsening of EEC of CL wearers using H2 O2 is attributed to H2 O2 scarce cleaning efficacy, which can be solved by adding a CL detergent solution. The origin of TF instability is found to be different. A remedy was found to be the administration of artificial tears, whose effect could be attributed either to the role of specific components or to rinsing and replacement of TF during wear.